Long-Chain Modification of the Tips and Inner Walls of MWCNTs and Their Nanocomposite Reverse Osmosis Membranes - Qing Li; Dengfeng Yang; Qingzhi Liu; Jianhua Wang; Zhun Ma; Dongmei Xu; Jun Gao (Membranes, 2022)
Multi-walled carbon nanotubes (MWCNTs) were modified on the tips and inner walls by 12-chloro-12-oxododecanedioic acid-methyl ester groups and then added to the polyamide composite membranes to prepare MWCNT-CH2OCOC12H23O2 membranes for desalination. The characterization results of transmission electron microscopy, Fourier transform, infrared transform, and thermogravimetric analysis showed that the 12-chloro-12-oxododecanedioic acid-methyl ester group was successfully grafted to the entrances and inner walls of the MWCNTs. The performance of the MWCNTs’ composite membranes was evaluated by scanning electron microscopy, contact angle, and filtration test. The modified membrane morphology is more uniform, and there is no structural damage. The grafting of carbon nanotubes with methyl 12-chloro-12-oxydodecyldicarboxylate could improve the hydrophilicity of the membrane. Under identical conditions, the water flux of MWCNT-CH2OCOC12H23O2 membranes was higher than that of the pristine carbon nanotube’s membrane, and the desalination rate was also slightly improved.